2017
DOI: 10.1016/j.rmed.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Omalizumab therapy in allergic bronchopulmonary aspergillosis: A synthesis review of published literature

Abstract: Omalizumab, a humanized mAb that binds to IgE, has been an effective therapy for patients with severe allergic asthma; however, there are few clinical trials examining the efficacy of Omalizumab in patients with allergic bronchopulmonary aspergillosis (ABPA) except some case reports. To assess the clinical and immunological effects of Omalizumab in ABPA patients, we made a synthesis review of 102 cases from 30 published literature, analyzed the effects of Omalizumab therapy in ABPA and conducted subgroup analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 58 publications
(52 reference statements)
0
61
0
2
Order By: Relevance
“…Recently in China, Li JX et al found that Omalizumab treatment is effective not only in decreasing IgE levels but also causes reduction in steroid requirement and improves pulmonary functions. 13 In present case, we could not use omalizumab due to its limited availability and financial recourses and only a combination of steroids and itraconazole provided excellent results.…”
Section: Case Reportmentioning
confidence: 68%
“…Recently in China, Li JX et al found that Omalizumab treatment is effective not only in decreasing IgE levels but also causes reduction in steroid requirement and improves pulmonary functions. 13 In present case, we could not use omalizumab due to its limited availability and financial recourses and only a combination of steroids and itraconazole provided excellent results.…”
Section: Case Reportmentioning
confidence: 68%
“…9 A review of 102 published cases of ABPA treated with omalizumab concluded that the drug helped mitigate symptoms, improve PFTs, and decrease corticosteroid requirements. 10 With the increasing use of omalizumab in refractory ABPA, there is interest in developing monoclonal antibodies that target other portions of ABPA's inflammatory cascade. Antieinterleukin 5 therapy (mepolizumab) has shown promising anecdotal results, demonstrating better symptom control, particularly when used in conjunction with omalizumab.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of asthma, omalizumab dose is adjusted according to serum IgE levels, whereas it is difficult to regulate its dose because of already higher serum IgE levels in ABPA. Based on clinical experience, and a limited number of studies, subcutaneous 375 mg omalizumab twice a month is another alternative treatment option in ABPA cases [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%